Feeds and fodder dynamics in selected river basins of Bangladesh (Bangladesh Journal of Animal Science, 2018)
A baseline survey was conducted with the objectives to determine seasonal availability, utilization of feeds and fodder resources and livestock production systems in different river basin areas and to identify the constraints of fodder production in selected river basins of Bangladesh. Based on cattle population, 2 upazilas from each of 10 districts were selected for household survey (HHS). A randomly selected 50 farmers from each upazila were considered for collecting information. After screening a total of 963 HHs were considered for statistical analyses. Results show that about 51%HHs were landless. Having an average population size of 3.3, about 99% HHs in the surveyed areas was keeping cattle, whereas, buffalo was not found in all regions which were found only in1.7% HHs with an average population size of 2.31 per buffalo keeper HH. Sheep was found only in about 1% HHs with an overall number of 3.22 per sheep keeper HH. About 16% HHs were keeping goats with an average size of 2.9 per sheep keeper HH. Significant differences on performance potentials were found both in native and crossbred cows among different regions. It was observed that all types of farm categories HHs reared cattle and most of them reared by tethering (around 23%) and free grazing (around 22%) management systems but semi-grazing was followed by around 14% HHs. Rest of the farmers followed different combinations of methods. Rice straw and naturally grown green grasses were the main roughages for feeding their cattle. About 95% HHs fed rice straw and about 81% HHs fed cut and carry green grass to their cattle. There were no seasonal variations on feeding rice straw but variations occurred for supplying cut and carry green grasses. Concentrates provided to animals in the surveyed areas were mainly rice polish, wheat bran, broken rice, pulse bran and mustard oil cake, among which rice polish and wheat bran were supplied by more HHs (about 93% and 75%, respectively). The variations of supplying concentrates among seasons were very negligible. Although, there were about 1.14% HHs who cultivated some fodder crops, they harvest grains for human consumption and residues for their cattle. However, high yielding varieties of fodders are very rarely cultivated by the farmers for feeding cattle in the riverside regions. The reason not to cultivate fodder and main constraint behind it was not accurately mentioned by the farmers. In the survey among different riverside regions, about48 different native green fodders were obtained in different agro-ecological zones, among which most available native green fodders were Durba, Badla, Kawn, Shama, Khesari, Gamma, Ura, Gobra, Shama and Maskalai. Most of the native grasses are grown more in summer and some others like Kawn, Khesari and Maskalai are grown in winter. Finally, it may be concluded that extensive fodder cultivation program by motivating farmers through training and demonstrating high yielding fodder crops are essential in the riverside regions for increasing productivity of livestock in the respective areas.Bang. J. Anim. Sci. 2017. 46 (3): 206-214